Exploring the Relationship Between Health Insurance Literacy and Health Equity Among College Students: A Pilot Study - Wynn, K. Jaelyn (East Carolina University)
Health insurance literacy is a critical factor that should be addressed in the college student population. This population has been found to have lower health insurance literacy levels, which can impact health outcomes. This study examines health insurance literacy and health equity among undergraduate college students at a Minority-Serving Institution (MSI) and a Predominantly White Institution (PWI) and examines demographic factors in health insurance literacy. A total of 276 students participated in a survey examining perceptions of health equity and health insurance literacy levels using items from the Kaiser Family Foundation (KFF). Bivariate associations were assessed using Mann-Whitney U tests, Chi-Square tests (or Fisher-Freeman-Halton tests as appropriate), and Spearman correlations. Multiple linear regression models were used to control for covariates in comparisons. Results found that students at the PWI had significantly higher mean health insurance literacy scores than students at the MSI (PWI Mean = 4.33 vs. MSI Mean =3.14, p=0.027) after controlling for student demographics. Perceptions of health equity between the two institutions were similar. Prior knowledge of health insurance was found to be positively associated with health insurance literacy levels (p<0.001). The number of barriers that students reported, and experiences of unfair treatment was not significant between the two institutions. Additionally, it was found that age (p<0.001), race (p=0.003), and academic standing (p=0.005) were significantly associated with health insurance literacy levels among all undergraduate students in this study, regardless of institution. Additional research should be conducted to determine if educational programs should be implemented to improve health insurance literacy levels among the college student population. Age, race, and academic standing were found to be disparities that contribute to health insurance literacy in this study and should be explored in future studies. Addressing gaps in health insurance literacy will improve college students' overall understanding of health insurance and improve health equity.
Keywords: health insurance literacy; health insurance knowledge; health insurance literacy levels in college students; Health Equity; Insurance, Health; Literacy; Pilot Projects; Students